Prostate cancer research: tools, cell types, and molecular targets - Liu, Alvin Y. (Frontiers in Oncology, 2024)
By pathology, prostate tumors appear glandular, aglandular or nonglandular, and histologically unorganized. The Gleason system imparts a numerical value to tumor histology ranging from pattern 3 (G3) showing glandular differentiation, pattern 4 (G4) less glandular differentiation to pattern 5 (G5) no differentiation. 1 In large patient cohorts, Gleason scores (GS, sum of two predominant patterns) characterize 46% as GS3+3, 41% GS3+4, 11% GS4+3, and 2% GS4+4. 2 Thus, most tumors first diagnosed are differentiated, but could become less differentiated over time. Disease up-grading during active surveillance supports this conjecture. On average 5 years after initial diagnosis, treatment was administered to surveillance patients because of increase from G3 to G4. 3 What triggers loss of differentiation or dedifferentiation over the disease course remains unclear. For dedifferentiation, as indicated by Gleason upgrading, is correlated with poor outcome.